“Irresistible grace” of secularization: subject deconstruction/ reconstitution in the changing structure of authority (Economic and Political Thought, 2016)
The article analyses the concept of secularization as an element of discoursebetween knowledge and power, and as social practice constitutinga subject in a changing structure of power in the historic process. In thiscontext, the author proposes that, from a broad historical perspective, theReformation should be understood as a key event in the early modern periodwhen many existing points of reference to subjectivity such as social and religiousstructures, the essence of time and understanding history were moved.A subject experienced the fall of seemingly indestructible everyday practicesand former ways of living. This caused that subjectivity had to go through theprocess of deconstruction of inadequate self-perception in order to achieveepistemological maturity and reconstruct itself following new rules allowingfor practicing ethical existence. This centuries-long process of redefining thesubject recognising the changeable areas of the relation between authorityand knowledge that was started by the Reformation causes that secularizationdoes not have to be seen as the regression of subjectivity but as “irresistiblegrace” facilitating the self-recognition of a subject who is better prepared toactive presence that is under the pressure of constant change.